Building a Professional Career in Conditions of Continuous Education - N. L. Sokolova; T. Y. Tsibizova (Научный диалог)
It is reported that in the monograph “Scientific basis for professional career building and development” (2017), prepared by A. S. Sokolova and M. G. Sergeyeva, the problem of developing a system of formation and development of professional career of the worker, successful and demanded on the labour market, is covered. The book contains the author’s definition career forming training. The author’s model of this process is proposed by the example of career of high school teacher.